A Novel Method of Complexity Metric for Object-Oriented Software - Tong Yi; Chun Fang (International Journal of Digital Multimedia Broadcasting)
With the rapid development and wide application of multimedia technology, the demand for the actual development of multimedia software in many industries is increasing. How to measure and improve the quality of multimedia software is an important problem to be solved urgently. In order to calculate the complicated situation and fuzziness of software quality, this paper introduced a software quality evaluation model based on the fuzzy matter element by using a method known as the fuzzy matter element analysis, combined with the TOPSIS method and the close degree. Compared with the existing typical software measurement methods, the results are basically consistent with the typical software measurement results. Then, Pearson simple correlation coefficient was used to analyse the correlation between the existing four measurement methods and the metric of practical experience, whose results show that the results of software quality measures based on fuzzy matter element are more in accordance with practical experience. Meanwhile, the results of this method are much more precise than the results of the other measurement methods.